Utilisation of inland water transport system in South East Asian region - an overview of the prospect - Abd. Kader, Ab. Saman; Ahmad, Mohd. Zamani (2006)
The development and upgradation of river system for transportation activities has been significantly important in many countries due to their economic and environmental benefits. A proper integrated river management system has been formulated to address for the increasing demand for transport capacity. Besides transportation, human also use waterways for irrigation, drainage, hydropower generation, flood control, watershed treatment, water supply for industrial and domestic consumption, leisure and conservation of wildlife. Hence, the various relevant authorities rigorously involved direct or indirectly in river management system to cater for this needs. Thus, river management system can be regarded as a multipurpose management system aimed at providing and managing the river efficiently for transportation activity. Strategic partnership between different authorities will maximise the well being of the river system to operate effectively. Where possible, different river tributaries can be connected within the country or region to create a waterhighway for economic as well as environmental prosperity between bordering nations in the South East Asian region where the existing of many mighty rivers such as Irrawady in Myanmar, Mekong in Vietnam, Rajang in Malaysia, Menam Chao Phraya in Thailand, Mahakam in Indonesia etc can be connected together for creating a grand water highway for cargo movement, passenger transportation, leisure and tourism. The European experience in creating the integrated inland waterways system for the region have been considered as a successful the model to be adopted. This paper discusses briefly on the prospect of IWT in the South east region in future as an integrated IWT system that for the economic as well as social well being.